Universal service obligation - Safinaz Mohd Hussein (Fakulti Undang - Undang, 2002)
Communications tools are very fundamental in the everyday lives of human being especially in this digital era. One of the important communications tools is telecommunications. Universal service is an obligation placed on telecommunications service providers to ensure that basic service is reasonably accessible to all people in a particular society. This paper discusses the meaning of universal service and its application in Malaysia